Meta-Learning on Graph with Curvature-Based Analysis (Student Abstract) - Moon, Tae Hong; Lim, Sungsu (Proceedings of the AAAI Conference on Artificial Intelligence, 2020)
Learning latent representations in graphs is finding a mapping that embeds nodes or edges as data points in a low-dimensional vector space. This paper introduces a flexible framework to enhance existing methodologies that have difficulty capturing local proximity and global relationships at the same time. Our approach generates a virtual edge between non-adjacent nodes based on the Forman-Ricci curvature in network. By analyzing the network using topological information, global relationships structurally similar can easily be detected and successfully integrated with previous works.